INOVASI DAN PENGEMBANGAN EVALUASI KURIKULUM PENDIDIKAN - Rici Vidiono Puperta Agus; Iswantir M (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Islamic education is essentially oriented towards the internalization of religious values to produce a kaffah (comprehensive) Muslim generation with a solid foundation of faith. This research examines the urgency of innovation and development in the evaluation of the Islamic education curriculum to address these challenges. Employing a library research approach, this study analyzes various relevant literatures and textbooks as the primary data sources. The main objective of this study is to dissect the basic concepts, objectives, and significance of the renewal and evaluation of the Islamic education curriculum. The results indicate that the evaluation system in Islamic education has a strong philosophical attachment to the principles of the Qur'an, where assessment benchmarks require a balance between scientific mastery and the formation of religious behavior. Therefore, innovation and development of curriculum evaluation are absolutely necessary so that indicators of student success are not reduced solely to the cognitive domain, but also comprehensively encompass the affective, psychomotor, and spiritual domains.